How outward FDIs affect income: Experiences from Chinese city-regions - Ruilin Yang; Harald Bathelt (ZFW - Advances in Economic Geography, 2023)
While outward foreign direct investments (OFDIs) shift resources from a home economy to foreign destinations, increased market and resource access as well as technological and knowledge effects in return have positive impacts on the home region. Such effects may be especially important in emerging contexts, such as that of China. Analyzing data of 285 Chinese city-regions, this paper investigates the impact of OFDIs on home-region income. We show that foreign investment activity positively and significantly impacts income levels in the home region, with differentiated effects depending on the knowledge characteristics of investments and regional absorptive capacity.
Keywords: 330; China; emerging markets; home-region investment impact; outward foreign direct investments (OFDIs); reverse investment effect